CHARACTERIZATION AND FERTILITY CAPABILITY CLASSIFICATION OF THE SOILS OF SHASHA RIVER FLOODPLAIN, OSUN STATE, NIGERIA - F., Adisa K.; O., Ojetade J.; A., Muda S.; A., Amusan A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
Characterization and fertility capability classification of soils of a floodplain in Osun State, Nigeriawere carried out. Soil samples from horizons of identified mapping units were analyzed for theirproperties. Soils were grouped based on their fertility capabilities. Soil texture ranged from sandyloam to sandy clay loam in the upper and mid basins while the basin floor was sandy loam. The soilswere slightly to strongly acidic, organic matter content ranged from low to high, available phosphoruswas low, while the exchangeable bases were high. The soils were characterized by the fertilityindicators: Lhkig for upper basin, Lir++g for mid basin and Lkig for basin floor. The agronomicconstraints of the soils include high acidity, low P content, low nutrient reserve, gravelly condition andgleying. Sustainable management of the soils would require efficient soil management systems througheffective drainage, liming and fertilization with the use of bed and mound